Strategi Pemulihan Keberlanjutan dan Ketangguhan Pariwisata Menghadapi Krisis - I Gusti Agung Ayu Gita Pritayanti Dinar; I Nyoman Gede Sugiartha; Kade Richa Mulyawati (Fakultas Hukum, Universitas Warmadewa, 2022)
Culture-based tourism is one of the sustainable tourism assets that contains unique cultural and natural traditions in an area. If we explore it more deeply, each village must have its own charm that contains various objects as noble values that can inspire tourists to village-based destinations, known as sustainable tourism. Bali as a tourism destination, known for its strong culture, pays serious attention to the sustainable tourism. One of the tourist villages in the area is Carangsari Village, which is located in Badung Regency. The village is trying to restore the tourism sector which has become the focus of the village community after it was stopped due to the spread of the corona virus. Motivated by the condition, this study is made to discuss the ideal recovery strategy for a sustainable tourism sector in the Carangsari village, Bali. This study makes use of an empirical legal research method with a statutory approach and an analysis of legal concepts. The results of this study indicate that a simple ideal recovery strategy is to add a schedule of sacred rituals in the tourist calendar in addition to the schedule of festivals existing in Bali.